Dynamic Panel Data Analysis of Income Inequality in Indonesia - Syafitri, Allichia Errika; Endang, Endang; Susilo, Joko Hadi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2025)
Research Originality: This study examines the short-term and long-term relationships between macroeconomic variables and income inequality, adopting a broader approach than previous research, which has primarily focused on partial and simultaneous influences on income inequality.Research Objectives: This study aims to analyze the dynamic variables that affect income inequality in Indonesia.Research Methods: This study uses panel data from 34 provinces in Indonesia from 2015 to 2023 and employs the Generalized Method of Moments Arellano Bond (GMM-AB) approach. This method was selected to address endogeneity and heteroscedasticity issues commonly encountered in panel data analysis.Empirical Results: The findings reveal that the Indonesian Democracy Index and the Gender Inequality Index significantly impact income inequality. Meanwhile, the ICT Development Index and the Human Development Index also exhibit significant influences. These results reinforce the argument that enhancing access to education and promoting gender equality are essential strategies for reducing income inequality.Implications: The study provides valuable insights for policymakers, emphasizing the need to strengthen democratic institutions and empower women through improved access to education and economic opportunities as key measures to mitigate income inequality.JEL Classification: D63, J16, O15, O32, P16How to Cite:Syafitri, A. E., Endang, E., & Susilo, J. E. (2025). Dynamic Panel Data Analysis of Income Inequality in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 149-162. https://doi.org/10.15408/sjie.v14i1.44943.